The reading to learn pedagogy in South African inclusive English First Additional Language classrooms: successes and challenges - Moyo, Sheron (Rhodes University, Faculty of Humanities, Institute for the Study of English in Africa)
Reading to Learn (RtL) has been frequently suggested for students not meeting grade-appropriate reading standards. However, its achievements and shortcomings have not been examined in inclusive education. In light of this, the main goal of this study was to explore the successes and challenges of this methodology in grade 9 English First Additional Language (FAL) inclusive classrooms across four schools in the Northern Cape Province's John Taolo Gaetsewe District. In light of the grave concerns about literacy development in South African schools, this methodology was created to fulfil the literacy needs of students from underprivileged groups in Australia. This qualitative study was grounded in social constructivist theory and an interpretative paradigm. The research used an exploratory case study comprising four participants who were purposively recruited and empowered with RtL between 2016 and 2022. The data-gathering methods used were semi-structured interviews, focus group discussions, and classroom observations to get insights into the achievements and shortcomings of the RtL pedagogy in inclusive classrooms. The qualitative data in this study was analysed using thematic analysis. The study's findings revealed that the RtL pedagogy gave students who faced reading obstacles in inclusive classes the skills needed to read, read with meaning, and improve as readers and writers through its six-step scaffolding interactive cycle. There were challenges in employing the RtL pedagogy in inclusive classes, such as it is time-consuming and makes it difficult for teachers to adhere to the time frame stipulated by the annual teaching plan. Nevertheless, the study's findings showed that the advantages of the RtL pedagogy outweigh the challenges.
Keywords: Reading (Secondary) -- South Africa Northern Cape; Reading comprehension; English as a second or foreign language; Inclusive education -- South Africa Northern Cape; High school students Social conditions